Impaired Self-Awareness and Denial During the Postacute Phases After Moderate to Severe Traumatic Brain Injury - Prigatano, George P.; Sherer, Mark (Frontiers in Psychology, 2020)
While a number of empirical studies have appeared on impaired self-awareness (ISA) after traumatic brain injury (TBI) over the last twenty years, the relative role of denial (as a psychological method of coping) has typically not been addressed in these studies. We propose that this failure has limited our understanding of how ISA and denial differentially affect efforts to rehabilitate persons with TBI. In this selective review paper, we summarize early findings in the field and integrate those findings with more recent observations (i.e., 1999-2019). We believe that this synthesis of information and expert clinical opinion will inform future research on ISA and denial as well as approaches to rehabilitation for persons with TBI.